Спортивная метафора в текстах газетной печати ХV Международного конкурса имени П. И. Чайковского - Dzienisiewicz, Maria (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article presents the analysis of the examples of metaphor of sport in classical music. The material of the above-mentioned phenomenon has been extracted from the press of The XV International Tchaikovsky Competition. The purpose is to describe the examples of sports terminology used as a metaphor in classical music competitions context. The studied material is divided into six lexical-thematic groups. The analysis focuses on Russian nouns, however, the article is complemented with examples of adjectives and verbs. The analyzed material shows that sports terminology can be applied successfully in depicting musical events such as The XV International Tchaikovsky Competition.